Uma proposta de implantação de gestão ambiental no laboratório de análises de solos da UFSM - Assumção, João Carlos Maciel de (2008)
The concern with the environmental performance comes demanding a different posture for the organizations from those that came more and more being adopted in the last decades. The governments' pressures, fiscal control organs and the population in general display it selves more accentuated than never. The Higher Education Institutions (IES), its schools, centers, departments and laboratories until some time were out behind of this scene of sustainable development. The environmental management with the residues managing and other environmental aspects constitute basic tools so that a positive environmental performance being reached. This study delineates as objective to propose a model of environmental management for the Laboratory of Analysis of Soil (LAS) belonging to Universidade Federal de Santa Maria. The methodology applied was a qualitative exploratory research with bibliographical investigation, with case study technique. The data collect was through non-structured interview and unsystematic individual observation as well as assisted by employees starting from visitations to the LAS. The sampling adopted method was the type of intentional no-probabilistic, considering the analysis of the last three years. The collected data were analyzed and worked; moreover, an initial environmental evaluation was made contemplating the following items: legislation and applicable environmental regulations, environmental aspects and impacts, evaluation of practices and existent procedures, and backward-analysis of incidents, including environmental passive. With that, suggestions and proposals were established, as the creation of an environmental policy for the LAS; indicators as the quantification and study of the techniques, reagents and solutions used; action plans as a program of managing of safety. Thus, this proposal intends to bring an safety and environmental fitting to the LAS and to serve as a management base model to other attached or not laboratories of the Rede Oficial de Laboratórios de Análise de Solos dos Estados do Rio Grande do Sul e Santa Catarina (ROLAS), originating benefits to those involved and the society.